On the Reversibility and Fragility of Sodium Metal Electrodes. Issue 39 (4th September 2019) - Deng, Yue; Zheng, Jingxu; Warren, Alexander; Yin, Jiefu; Choudhury, Snehashis; Biswal, Prayag; Zhang, Duhan; Archer, Lynden A.
Abstract: Metallic sodium is receiving renewed interest as a battery anode material because the metal is earth‐abundant, inexpensive, and offers a high specific storage capacity (1166 mAh g −1 at −2.71 V vs the standard hydrogen potential). Unlike metallic lithium, the case for Na as the anode in rechargeable batteries has already been demonstrated on a commercial scale in high‐temperature Na||S and Na||NiCl2 secondary batteries, which increases interest. The reversibility of room temperature sodium anodes is investigated in galvanostatic plating/stripping reactions using in situ optical visualization and galvanostatic polarization measurements. It is discovered that electronic disconnection of mossy metallic Na deposits ("orphaning") is a dominant source of anode irreversibility in liquid electrolytes. The disconnection is shown by means of direct visualization studies to be triggered by a root‐breakage process during the stripping cycle. As a further step toward electrode designs that are able to accommodate the fragile Na deposits, electrodeposition of Na is demonstrated in nonplanar electrode architectures, which provide continuous and morphology agnostic access to the metal at all stages of electrochemical cycling. On this basis, nonplanar Na electrodes are reported, which exhibit exceptionally high levels of reversibility (Coulombic efficiency >99.6% for 1 mAh cm −2 Na throughput) in room‐temperature, liquid electrolytes. Abstract : In situ optical visualization of sodium (Na) electrodeposition shows Na deposits as low‐density, mossy structures over a range of current densities. The structures easily break to produce electronically disconnected Na and poor anode reversibility. A nonplanar electrode architecture, which provides morphology agnostic access enables Na electrodes with exceptional reversibility.